The Implementation of the Game-Based Learning Model through Kahoot on Mathematics Learning Outcomes of Students at SMP Negeri 2 Loceret - Eka Fadhilah; Addin Zuhrotul Aini; Reza Dimas Pravangasta (Kirana Publisher (KNPub), 2025)
The mathematics ability of students in Indonesia remains low, as shown by PISA and TIMSS results. One contributing factor is conventional teaching methods that do not actively engage students. This study aimed to examine the difference in mathematics learning outcomes on Data and Diagram material between conventional learning and Game-Based Learning using the Kahoot application for seventh-grade students at SMP Negeri 2 Loceret in the 2024/2025 academic year. A quasi-experimental method with a Post-test Only Control Group design was used. The population included 109 students, with purposive samples: class VII-A (32 students) as the control group and VII-B (26 students) as the experimental group. The instrument was a 16-item multiple-choice post-test. Data were analyzed using descriptive and inferential statistics, including normality, homogeneity, and t-tests. The experimental class scored higher (77.27) than the control class (60.00), with a significance value of 0.000 (<0.05), indicating a significant difference. Game-Based Learning through Kahoot effectively improves mathematics learning outcomes.